Connecting research, management, education and policy for the conservation of armadillos in the Orinoco Llanos of Colombia - Superina, Mariella (2019)
Successful conservation actions require strategies that combine research, policy formulation and enforcement, practical interventions and education. Here we review the Armadillo Conservation Programme, which was initiated in 2012 as a pioneering multidisciplinary programme for the conservation and management of five armadillo species in the Orinoco Llanos of Colombia. It is led by a multi-institutional alliance that ensures active participation of stakeholders during all stages of the programme. Six main threats affecting armadillo populations in the Llanos were identified, and these were addressed in the first joint action plan of two Colombian environmental authorities. Scientific research facilitated an increase in the knowledge available about the armadillos of the Llanos, and the recategorization of the northern long-nosed armadillo Dasypus sabanicola on the IUCN Red List. Threat evaluation and mitigation included the assessment of illegal bushmeat trade and consumption in local restaurants and the establishment of a certification label for restaurants that do not sell wild meat. Multiple strategies were used to raise awareness about armadillos and position them as flagship species for the Llanos, including education programmes in schools, travelling exhibitions, talks at universities, and the publication of several books. The local communities were actively involved through a network of private reserves committed to the conservation of armadillos, in which armadillos are protected from poaching and monitored by farmers. Breeding and rehabilitation facilities were established that can host confiscated armadillos and raise awareness among the local communities. This case study shows that conservation programmes targeted at inconspicuous and poorly known species can be successful.